Adaptation of trabecular bone to very high mechanical loads - Claes, L.; Reusch, M.; Wehner, T.; Dürselen, L.; Ignatius, A. (Osteologie, 2014)
It is well known that bone adapts to increased mechanical loading by the apposition of newly formed bone. The correlation between load-induced bone stress and strain with bone formation has often been investigated in cortical bone, however, little is known about this relationship in trabecular bone. In particular, nothing is known about trabecular bone adaptation in response to very high mechanical loading close to its fatigue load. Here, we investigated trabecular bone formation in a sheep osteotomy model of the femoral condyle in a region of interest close to the osteotomy, where local stresses in the range of the fatigue strength of trabecular bone occurred. After eight weeks, the trabecular bone volume and the mineral apposition rate increased two-fold and threefold, respectively, at this highly loaded location, compared to the corresponding region of interest in intact femoral condyles under physiological loading. This study demonstrated, for the first time, the remarkable capability of trabecular bone to adapt to stress and strain close to its failure load.
Keywords: Bone adaptation; mechano-biology; bone formation; strain